IDENTIFIKASI KARAKTERISTIK PERMUKIMAN KUMUH DI KAWASAN KOTA DENPASAR (STUDI KASUS PERMUKIMAN JALAN KARYA MAKMUR, UBUNG KAJA, DENPASAR UTARA) - TJOKORDA ISTRI PRAGANINGRUM (GANEC SWARA, 2024)
The increase in population impacts the need for space in Denpasar City. In this study, the need for space is related to the need for housing. A misalignment of the economic level of the community follows the high demand for residential space. This eventually led to the problem of the slum phenomenon. This research was conducted to determine the characteristics and causes of slums in the Denpasar City Area with a case study of Jalan Karya Makmur, North Denpasar. This research uses a qualitative method approach with a naturalistic paradigm. The data used was obtained directly by carrying out observations and documentation at the research location. Data collection techniques use non-participant observation techniques which are carried out by observing while understanding and analyzing the phenomena contained in the research location. Based on the research obtained that the characteristics of slums seen from the condition of the building have a high density and use semi-permanent materials, at the location of the use of clean water comes from drilled wells and is used together, environmental roads tend not to use pavement, drainage is not able to drain water properly, waste conditions are not managed properly, household waste is directly channeled into existing channels and lack of protection against fire hazards. The factors that cause slums are residential density, economic capacity of the community, flammable building materials, and lack of public awareness in environmental management.